Truly Catalytic Gewald Synthesis of 2-Aminothiophenes Using Piperidinium Borate (Pip Borate), a Conjugate Acid–Base Pair - Gavali, Kanchan D.; Chaturbhuj, Ganesh U. (SynOpen, 2023)
The Gewald reaction has been well-known for more than half a century as an excellent method to provide bioactive 2-aminothiophene heterocycles from the reaction of carbonyl compounds, α-cyanoacetates, and elemental sulfur, in the presence of amines, in stoichiometric amounts. This work describes the use of salts of boric acid as conjugate acid-base pairs in a truly catalytic amount for the cyclocondensation of ketones with active methylenes such as malononitrile, ethyl cyanoacetate, and benzoyl acetonitrile with sulfur to give 2-aminothiophenes via the Gewald reaction. The present protocol is also applied for synthesizing Tinoridine, an anti-peroxidative NSAID, with excellent yield. Additionally, the catalyst has great recyclability and reusability.
Keywords: conjugate acid-base catalyst; Gewald reaction; 2-aminothiophenes; recyclable; piperidinium borate